Fourier-domain optical coherence tomography evaluation of retinal and optic nerve head neovascularisation in proliferative diabetic retinopathy. Issue 1 (24th October 2013) - Muqit, Mahiul M K; Stanga, Paulo E
Abstract : Aim: To describe the in vivo spatial and morphological vitreoretinal relationships associated with diabetic retinal neovascularisation using Fourier-domain optical coherence tomography (FD-OCT). Methods: Qualitative assessment of macula, retina and optic disc head FD-OCT (Topcon 3D OCT-1000) imaging of patients with treatment-naive and laser-treated proliferative diabetic retinopathy (PDR). The morphology and plane of retinal neovascularisation at the disc (NVD) and elsewhere in the retina (NVE) were examined, and the posterior vitreous relationships were evaluated. The FD-OCT characteristics of clinical versus subclinical PDR disease were correlated with conventional and wide-field Optos fundus fluorescein angiography. Results: 50 eyes of 50 patients were evaluated in this retrospective study. Retinal neovascularisation appears as a hyper-reflective complex, with NVE arising from inner retina with disruption through the internal limiting membrane to attach to the posterior hyaloid surface. FD-OCT detected subclinical hyper-reflective NVD complexes that were subvisible on colour fundus imaging. We describe retinoschisis, vitreoretinal adhesions and pegs, zones of separation, and intraretinal tractional elements in untreated PDR patients using high resolution FD-OCT. Conclusions: FD-OCT can non-invasively characterise retinal and optic nerve head neovascular complexes at different stages of the proliferative disease process. In clinical practice, FD-OCT can monitor the in vivo serial changes of retinal neovascularisation over time.